PENGETAHUAN PERAWAT TENTANG CARING BEHAVIOR DI PUSKESMAS TIGARUNGGU KABUPATEN SIMALUNGUN TAHUN 2021 - Mestiana Br Karo; Rusmauli Lumban Gaol; Devi Arta Sumbayak (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Caring is a moral attitude in nursing practice, the caring nature of nurses when dealing with sick people. The nurse must show that the nurse cares about the patient's condition. Caring is a fundamental concept of nursing that will describe a caring behavior person. Caring behavior is a way or behavior of nurses to patients, do not be indifferent to patients, do not discriminate against patients, both in terms of age, economy, culture, and religion. In general, caring behavior is a habit that nurses do when providing nursing care to patients. The purpose of the study was to determine the knowledge of nurses about caring behavior at Tigarunggu Health Center, Simalungun Regency in 2021. This study used a qualitative method where data collection was carried out by interviewing as many as 5 questions to be able to dig deeper into a knowledge of caring behavior. The sampling technique used a total sampling of 8 respondents. The data analysis technique used is thematic analysis. The results obtained: caring is a sense of caring for the patient and the patient's family, providing good nursing care, approaching, and being able to feel the pain experienced by the patient. Caring behavior is a habit that nurses do when providing nursing care to patients. How to provide caring behavior in nursing practice by getting closer to the patient, touching the patient, asking what is sick, and applying the 3S, namely smile, greet, and touch. The benefit of caring behavior is that the patient will feel satisfied with the treatment so that the patient feels the pain has reduced. The obstacles faced when practicing caring behavior are when the nurse is friendly, caring, has tried her best to the patient, but the patient refuses or is indifferent to the nurse.